Multiple Dynamic Perimeter Surveillance by an Autonomous Robot - Barros, Vítor; Macharet, Douglas (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
This paper proposes a method to perform surveillance tasks of dynamic perimeters using an autonomous mobile robot. In natural disaster scenarios in which the borderline of the hazard like oil spills, wildfire, and radiation can expand over time and pose a lot of danger, it is extremely helpful to efficiently perform a surveillance task in order to support evacuation missions and to aid the hazard dispel. Our proposal is based upon using an interpolation method to define the boundary of the perimeter that will be placed under surveillance, next a navigation strategy makes the robots converge to and circumnavigate the defined perimeter, finally, an optimization approach improves the coverage considering multiple perimeters. Results show that our perimeter representation is reliable in different scenarios, and the motion control approach allows for an efficient and minimized tracking error.